1988
DOI: 10.5511/plantbiotechnology1984.5.72
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Callus from Pistils of Crocus sativus L. and Production of Color Compounds in the Callus

Abstract: The calli were induced from the pistils of saffron. MS, 1/2 MS, and NN medium with BA and NAA at 1 mg/l each were the most effective for the induction and growth of the calli. The calli produced crocin, crocetin-di (monoglucosyl-diglucosyl) ester and crocetin-di (monoglucosyl) ester. The calli producing those pigments have been maintained for more than two years under dark conditions. Saffron, Crocus sativus L., was originated from south Europe and has been recognized for its medicinal properties for a long ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The concentration of crocin and picrocrocin in TC stigmas was lower by 6 and 11 times respectively than the natural stigmas. Such a trend in the pigment composition was also observed in earlier studies (Hori et al 1988;.…”
Section: Ovary Explantssupporting
confidence: 73%
See 1 more Smart Citation
“…The concentration of crocin and picrocrocin in TC stigmas was lower by 6 and 11 times respectively than the natural stigmas. Such a trend in the pigment composition was also observed in earlier studies (Hori et al 1988;.…”
Section: Ovary Explantssupporting
confidence: 73%
“…It grows under specific climatic conditions and the harvesting of flowers needs skilled labour, which leads to the high cost of this spice. Attempts have been made to induce saffron in tissue cultures from stigmas (Hori et al 1988;Sarma et al 1990) and ovaries . Recently Fakhrai & Evans (1990) induced stigma-like structures successfully by using different floral explants of Crocus sativus.…”
Section: Introductionmentioning
confidence: 99%
“…The use and demand of saffron are increasing, but its world production is low compared to the demand, due to the high cost of production. Many in vitro cultures and biotechnological experiments have been performed to produce crocetin glycosilated derivatives and other saffron components Hori et al, 1988;Sarma et al, 1991) and new techniques have been applied to analyse saffron (Amelotti & Mannino, 1977;Basker & Neghbi, 1983. Recently, corms and leaves of Crocus sativus have also been investigated as a source of new important compounds of medicinal and industrial use (Escribano et al, 2000;Bergoin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (1996) reported biotransformation of ferulic acid vanillamine to capsacin and vanillin in immobilised cell cultures of Capsicum frutescens. Reports on the in vitro synthesis of crocin, picrocrocin and safranel from saffron stigma (Himeno and Sano, 1995) and colour components from cells derived from pistils (Hori et al, 1988) are available for further scaling up. Callus and cell cultures were established in nutmeg, clove, camphor, ginger, lavender, mint, thyme, celery etc.…”
Section: Callus and Cell Culture Systemsmentioning
confidence: 99%